Case Report: Ruptured Middle Cerebral Artery Aneurysm With Intrasylvian Hematoma Successfully Treated by Coil Embolization and Minimally Invasive Puncture and Drainage - Li, Zhen; Hu, Quan; Zhao, Li; Huang, Huayun; Zhang, Shizhong; Zheng, Limin; Wang, Guojun (Frontiers in Neurology, 2021)
Objective: The incidence of intracerebral hematoma among patients with aneurysmal subarachnoid hemorrhage is up to third of the cases (12%–35%).Ruptured middle cerebral artery (MCA) aneurysm with hematoma usually accompanied by progressive cerebral swelling with poorer outcomes.We successfully treated ruptured middle cerebral artery aneurysm with intrasylvian hematoma by coil embolization and minimally invasive puncture and drainage. Methods: From 2012 February to 2019 March, 6 aneurysm surgeries for ruptured MCA aneurysms with intrasylvian hematoma were performed in our' clinic. All patients had intracranial hematomas less than 30 mL and GCS scores greater than 8. The patients were treated by coil embolization and minimally invasive puncture and drainage. Results: The aneurysms in all patients were completely embolized and the Hematomas were mostly removed by minimally invasive puncture. The GOS of all patients were more than 4 when they discharged. Conclusions: Coil Embolization and minimally invasive puncture and drainage is a viable treatment for ruptured middle cerebral artery aneurysms with Hematomas, especially if the patient is too old or complicated to undergo craniotomy or is unwilling to undergo craniotomy, or patients at greater risk of surgery three days after bleeding.